METHODOLOGICAL STRATEGY FOR THE AXIOLOGICAL FORMATION ON THE FUTURES PROFESSIONAL / ESTRATEGIA METODOLÓGICA PARA LA FORMACIÓN AXIOLÓGICA DE LOS FUTUROS PROFESIONALES - Liván Álvarez Arzuaga; Melquiades Mendoza Pérez; Liana Fuentes Seisdedos (Didasc@lia: didáctica y educación, 2013)
The current article evidences a methodological strategy for the axiological formation on the future professionals. It was applied as consequence of some studies carried out on the Physical Culture Faculty. Taking into account the uttered difficulties in the social practice, it was considered a scientific investigation which projected, a methodological strategy directed to form a compromised and transcendent performance on the future professionals. It supports a system of actions focused on students and professors which, together with the methodological activities, favored the formative process in such sense, contributing to achieve an improved formative process, in which the student assumed, in a conscious and compromised form, its individual constructive process.